TERAPI PENYEMBUHAN AUTIS MELALUI PENDEKATAN KONVENSIONAL DAN ZIKIR DI PEKANBARU DAN YOGYAKARTA - Miftahuddin Miftahuddin; M Fahli Zatrahadi; Suhaimi Suhaimi; Darmawati Darmawati; Dea Aulia (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
On account of the development of science, there are recently many alternative treatments to cure autism through various kinds of therapies such as used by the Permata Hati Pekanbaru School and the Islamic Boarding School of Taruna Al-Quran in Yogyakarta. The purpose of the current paper was to determine healing therapy on autism through conventional and Dhikr approaches. Conducted through qualitative approach, the chosen subjects consisted of clients, therapists and client families. The results of this study showed that therapy through conventional approaches at the Permata Hati Pekanbaru School used 5 treatments; 1. Speech therapy, 2. occupational therapy, 3. social interaction therapy, 4. sensory interaction therapy, and 5. eating therapy. Otherwise, the Dhikr therapy in the Islamic Boarding School of Taruna Al-Quran in Yogyakarta noticed the results of the morning evening Dhikr through several stages; 1. assessment, 2. determining goals, 3. patterns of habitualizing behavior, 4. and changes in behavior. The project showed that the Permata Hati Pekanbaru therapy focused on physical health, while the Dhikr therapy focused on spiritual factors.